2010
DOI: 10.1088/0953-8984/22/22/226002
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological theory of phase transitions in multiferroic MnWO4: magnetoelectricity and modulated magnetic order

Abstract: The phenomenological theory of phase transitions in multiferroic MnWO₄ is suggested. The theoretical model uses the assumption that the magnetic order is driven by the instability in the (1/4;1/2;1/2) point of the Brillouin zone, which is justified by the symmetry of the low-temperature magnetic phase. It is shown that the experimentally observed incommensurate magnetic order is due to the Lifshitz invariants allowed for the corresponding order parameters. Invariants responsible for the magnetoelectric interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 22 publications
(57 reference statements)
3
31
0
Order By: Relevance
“…The magnetic phase transitions in wolframite were studied theoretically in a number of works [16,18,19,37,38]. In [16,18] the authors developed phenomenological models of phase transitions in MnWO 4 starting with the order parameters belonging to the incommensurate wave vector k inc .…”
Section: Mnwomentioning
confidence: 99%
See 4 more Smart Citations
“…The magnetic phase transitions in wolframite were studied theoretically in a number of works [16,18,19,37,38]. In [16,18] the authors developed phenomenological models of phase transitions in MnWO 4 starting with the order parameters belonging to the incommensurate wave vector k inc .…”
Section: Mnwomentioning
confidence: 99%
“…In our previous work [19] we developed a phenomenological model of phase transitions using magnetic order parameters belonging to the k c point of the Brillouin zone and accounted for the incommensurate phases by means of Lifshitz invariants. We also suggested that the phase transitions in wolframite be described starting from the orthorhombic praphase [19,20].…”
Section: Mnwomentioning
confidence: 99%
See 3 more Smart Citations